Ciclomorfose em Bosmina (Crustacea, Cladocera) no Lago Paranoá, Brasília - Elmoor-Loureiro, Lourdes M. A. (1989)
In order to verify the existence of seasonal variations in morphology of Bosmina longirostris and Bosmina hagmanni, samples were taken from Paranoá Lake (Brasília, DF) during 1983. Body length and breadth, antennule, mucro and eye diameter were measured. Alometry rates were also calculated. It was verified that throughout the year both Bosmina species presented variation involving the five measures. The measures, except the antennule and mucro of B. longirostris, depend, at least partially, on the size of the individual and, therefore, on the age structure of the population. The antennule and mucro variations of B. hagmanni were strongly related to alometry rates. For B. longirostris the antennule and mucro variations appeared to be related to phenomena in an embryonic phase.